Exploring the Pharmacokinetic Profile of Remifentanil in Mid-Trimester Gestations Undergoing Fetal Intervention Procedures - Smith, Judith A.; Donepudi, Roopali V.; Argoti, Pedro S.; Giezentanner, Anita L.; Jain, Ranu; Boring, Noemi; Garcia, Elisa; Moise, Kenneth J. (Frontiers in Pharmacology, 2017)
BACKGROUND: Indications for surgery during pregnancy have increased, which include both maternal and fetal. Specifically fetal interventions have increased from conditions that were considered lethal like twin twin transfusion syndrome and severe fetal anemia to non-lethal conditions like myelomeningocele. The optimal anesthetic agent for in utero surgery is yet to be determined. Currently remifentanil is used as preferred agent due to its short half-life however pharmacokinetics in pregnancy has not been evaluated. OBJECTIVE: To determine the pharmacokinetic parameters of remifentanil in a mid-trimester pregnant patient population undergoing fetal intervention. STUDY DESIGN: A liquid chromatography assay with ultraviolet absorbance was developed and validated to estimate maternal serum remifentanil levels. Serial blood samples were obtained at baseline and at selected time points: 5, 15, 30, 45, 60 minutes after the beginning of the remifentanil infusion and at 15, 30 and 60 minutes post end of infusion. RESULTS: Ten pregnant patients were enrolled in the study however only eight patients had sampling obtained at all time points. The mean gestational age was 22.2 (± 2.7) weeks, maternal age was 27.8 (± 5.1) years and body mass index was 29.6 (±6.3). After receiving a continuous infusion of remifentanil, mean total dose was 975.3 g, Cmin was 2.0ng/mL and Cmax was 8.4ng/mL. A two-compartment model best described the plasma remifentanil data. Mean pharmacokinetic parameters were: volume of distribution (Vdc)= 124.6L (16.2 -530.8L), maternal remifentanil total clearance (Clt) = 170.7L/hr (17.7-486.9L/hr), and half-life (t½) = 0.6hrs (0.2-0.9hr). The maternal remifentanil area under the curve (AUC) ranged from 2.7 – 21.7 g/L*hr. The mean alpha-acidic glycoprotein was 124.8 mg/dL (81.3-149.8). CONCLUSION: The pharmacokinetic profile of remifentanil in pregnant women is similar to previously reported profiles in the general population, but with differences in volume of distribution, clearance, half-life and AAG levels. This data did provide some potential rationale for the clinical observations why when remifentanil is dosed based on non-pregnant guidelines, it did not uniformly provide adequate fetal immobilization. These findings are important for the development of further clinical studies to optimize dosing for surgery during pregnancy including the estimation of placental transfer and potential total fetal